The importance of factorial design in tissue engineering and biomaterials science: Optimisation of cell seeding efficiency on dermal scaffolds as a case study. (21st June 2018) - Levin, Alexandra; Sharma, Vaibhav; Hook, Lilian; García-Gareta, Elena
This article presents a case study to show the usefulness and importance of using factorial design in tissue engineering and biomaterials science. We used a full factorial experimental design (2 × 2 × 2 × 3) to solve a routine query in every biomaterial research project: the optimisation of cell seeding efficiency for pre-clinical in vitro cell studies, the importance of which is often overlooked. In addition, tissue-engineered scaffolds can be cellularised with relevant cell type(s) to form implantable tissue constructs, where the cell seeding method must be reliable and robust. Our results show the complex relationship between cells and scaffolds and suggest that the optimum seeding conditions for each material may be different due to different material properties, and therefore, should be investigated for individual scaffolds. Our factorial experimental design can be easily translated to other cell types and three-dimensional biomaterials, where multiple interacting variables can be thoroughly investigated for better understanding of cell–biomaterial interactions.